A Theory of Monopolistic Competition with Horizontally Heterogeneous Consumers - Sergey G. Kokovin; Shamil Sharapudinov; Alexander Tarasov; Philip Ushchev (Center for Economic Studies and ifo Institute (CESifo), 2020)
Our novel approach to modeling monopolistic competition with heterogeneous consumers involves a space of characteristics of a differentiated good (consumers' ideal points), alike Hotelling (1929). Firms have heterogeneous costs à la Melitz (2003). In addition to price setting, each firm also chooses its optimal location/niche in this space. We formulate conditions for positive sorting: more efficient firms serve larger market segments and face tougher competition in the equilibrium. Our framework entails rich equilibrium patterns displaying non-monotonic markups, high in the most and least populated niches, and the unequal gains from trade across different consumers.
Keywords: F10; L11; L13; 330; firm heterogeneity; product space; positive sorting; product niches